The penal impact of community punishment in England and Wales: a conceptual and empirical study - Hayes, David John (2015)
This thesis examines two research questions: firstly, how does community punishment impact upon the lives of those subjected to it; and secondly, to what extent is that impact affected by the relationship between the offender and her Probation Service supervisor? It considers these questions in both conceptual and empirical terms by outlining, and then deploying, the analytical framework of penal impact, an approach to penal severity that uses pain as a metric by which to judge the suitability of punitive interventions. By evaluating sentence severity in terms of penal impact, one can examine both the types of pain that follow from a particular sentence, as well as their relative magnitude, building up a qualitative comparison of different impositions of community punishment.